Research of Thermal Effect of Cable-Stayed Bridge with a Separated Side-Box Steel-Concrete Composite Girder under Solar Radiation - Han-hao Zhang; Pei-zhi Wang; Shuanhai He; Yuan Li; Ke-fan Chen; Nan-nan Sun (Advances in Civil Engineering)
At present, there are few studies on the thermal effect of solar radiation on a separated double-sided box steel-concrete composite girder cable-stayed bridge. In this paper, the beam element and mixed element models are combined with the theory of transient heat transfer analysis and meteorology; this approach is adopted to carry out a thermodynamic analysis of a related bridge project. The calculation results of the thermal field and structural thermodynamic analysis of bridge sections show that, in terms of a separated double-sided box steel-concrete composite girder cable-stayed bridge, the thermal field distributions of the main girder and the pylons are extremely complex under conditions of solar radiation. Therefore, the real thermal field cannot be accurately described as a one-dimensional temperature gradient. The traditional beam element model cannot accurately simulate the temperature effect, and it will underestimate its thermal effect. The calculated temperature stress values of the mixed element model are quite different from those of the of beam element model. The mixed element model can precisely reflect the local thermal effect of each component in this system under solar radiation. Compared with the calculation results of the beam element model, the maximum temperature stress of the bridge deck in each section of the main girder is generally 20% larger; the maximum temperature stress levels of the steel-beam top and bottom plates are 14.7 MPa and 15.9 MPa larger, respectively. The maximum shear stress of the steel-concrete interface is 0.2 MPa larger. The research results of the temperature effect calculated by the mixed element have an important guiding significance for the design and maintenance of bridges.